MODEL WORK INTEGRATED LEARNING (WIL) DALAM PENDIDIKAN PROGRAM PKL DI SEKOLAH MENENGAH KEJURUAN KESEHATAN DI KOTA TANGERANG - basyit, abdul; husein, Turizal Husein; salim, Agus Salim; Hamsah Tis’ah, J. Anhar Rabi Hamsah Tis’ah; Gumelar, R Tommy Gumelar (ISLAMIKA, 2024)
ABSTRACT This study aims to find and prove (1) the Field Work Practice Program at Health Vocational High Schools in Tangerang City. (2) Barriers to the Field Work Practice Program and its Implementation in the World of Work for Health Vocational School Graduates in Tangerang City (3) Effective Collaboration Models in the Implementation of Health Vocational School Practice Programs in Tangerang City with the World of Work. This type of research is a qualitative research with a phenomenological approach. The location of this research was carried out at one of the Health Vocational High Schools (SMK) in the City of Tangerang Nursing Expertise Program. Data collection using in-depth interview techniques, observation, and documentation. The results of the study show that (1) there is still a weak relationship between educational institutions and the industrial world which leads to ineffective implementation, making it difficult for PKL participants to get jobs according to their competencies (2) Some obstacles to the Field Work Practice Proyahoo.comgram and its Implementation in the World of Work for Health Vocational School Graduates in Tangerang City is that there are still limited places for street vendors and there are still a number of Hospitals and Health Centers that refuse street vendors participants from Health Vocational Schools (3) The Work-Integrated Learning (WIL) model is able to improve the quality of the street vendors' experience and the right career choice and working together using the nucleus-plasma pattern, franchise pattern, general trade pattern, operational cooperation pattern, and partnership pattern.